Bullying Behaviour among Middle School Students in Rural and Town Communities - Erni Ratna Dewi (Bisma The Journal of Counseling, 2026)
The gap in access to information and the quality of education between urban and rural institutions motivated this study. This research on bullying aligns with the Indonesian government's commitment to address three key issues in education: bullying, intolerance, and sexual violence. This study aims to investigate factors influencing bullying behaviour among junior high school students directed at their peers in rural and urban communities. The study employed quantitative methods, with 715 students participating. Junior high school students were selected as the study sample due to the higher incidence of violence compared to senior high school students. Data collection was conducted using the Qualtrics system. The study findings indicate that student residence influences bullying behaviour, with students in rural communities engaging in less bullying than those in urban areas. Gender and grade level variables also significantly influence bullying behaviour among junior high school students in rural and urban communities across Indonesia. These findings imply the need for various bullying prevention and intervention strategies based on regional context, gender, and grade level so that national anti-violence programs in schools can be implemented more effectively and effectively. This study concludes that more targeted and contextual interventions tailored to regional characteristics and student groups are needed to support the national agenda of creating safe and violence-free educational environments. This research implies the need for contextual, region, gender, and grade-level bullying prevention strategies to make anti-violence policies in schools more effective and targeted.